Therapeutic Effects of Allium sativum and Allium cepa in Schistosoma mansoni experimental infection - Mantawy, Mona Mohamed; Ali, Hanan Farouk; Rizk, Maha Zaki (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
The effects of both garlic (Allium sativum) and onion (Allium cepa) on some biochemical parameters in Schistosoma mansoni infected mice individually and mixed either with or without the currently used drug, praziquantel (PZQ) were investigated. These involved some immunological parameters, namely IgM, IgG, interleukins 2 and 6 (IL-2 and 6) and tumor necrosis factor (TNF-α), some antioxidant enzymes [catalase, superoxide dismutase (SOD) and glutathione peroxidase (GPX)]. In addition, parasitological and histopathological investigations were performed. No changes were observed in the normal control mice treated with dry extract of onion or garlic, individually or mixed, with or without PZQ, compared to the normal healthy control group. Infection with S. mansoni showed an increase in IgG, IgM, IL-2, IL-6, TNF-α and catalase enzyme, accompanied with a decrease in GPX and SOD antioxidant enzyme activities. Remarkable amelioration was noticed in the levels of all the measured parameters in S. mansoni infected mice after administration of the studied extracts. Moreover a significant reduction in worm burden, hepatic and intestinal eggs and oogram count was noticed which was reflected in normalization of liver architecture.